TEACHER STRATEGIES FOR CULTIVATING CRITICAL THINKING WITHIN PROJECT-BASED LEARNING IN EFL SETTINGS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
As a result of today's globalization and rapid development of information technologies, the language learning process has become more complicated, and it is not enough to teach only grammatical rules or increase vocabulary. The formation of the ability to use the language effectively and purposefully in learners of English as a Second Language (EFL) is considered an important task. At the same time, critical thinking is one of the main skills that serve to develop students' ability to analyze, evaluate information, solve problems and find creative solutions (Paul & Elder, 2014).